A phytosociological study on the community of palaquium gutta (Hook.f.) Baill. (Sapotaceae) at Ayer Hitam Forest Reserve, Selangor, Malaysia - Abdul Razak, Sarah; Hamzah, Nur Adnilaila; Haron, Noorma Wati; Alias, Mohamad Azani (Penerbit Universiti Kebangsaan Malaysia, 2015)
A phytosociological study on the flora and vegetation community of Palaquium gutta (Hook.f.) Baill. was carried out in Compartment 13 of Ayer Hitam Forest Reserve, Selangor. The main objectives of this study were to identify, characterize and classify the P. gutta community which is naturally distributed in Ayer Hitam Forest Reserve. A total of 10 plots (30×30 m in size) were constructed according to the line transect method. The vegetation sampling and data analysis were done according to the Braun-Blanquet approach. The results showed that there were 59 species belonging to 54 genera and 34 families in the form of herbs, shrubs, understorey trees and also canopy tree layers. The most common species in the study area were P. gutta and Endospermum diadenum (Miq.) Airy Shaw. The phytosociological study identified a community of Palaquium gutta-Endospermum. diadenum along with two sub-communities known as Dracaena sp. sub-community and Streblus elongatus sub-community. The results also showed that most of the species belong to the Euphorbiaceae. This indicates that the forest is a secondary forest.